Comparative analysis of Indonesia's economic resilience in the Asia-Pacific context - Santoso, Feliks Y. E.; Samputra, Palupi L (Journal of Economic Resilience and Sustainable Development, 2024)
Background: economic resilience, defined as the ability of an economy to absorb and recover from shocks, is crucial for sustainable development. This study aims to assess and compare Indonesia's economic resilience with other Asia-Pacific countries in the post-COVID-19 era. Methods: Using Briguglio's theoretical framework, the study evaluates economic resilience through four key dimensions: macroeconomic stability, microeconomic efficiency, governance, and social development. Data from 2019 to 2023 were collected from international sources such as the World Bank, IMF, and UNDP. Finding: The results indicate that Indonesia consistently ranks lower on the Economic Resilience Index (ERI) compared to its regional peers. The country's underperformance is particularly evident in microeconomic efficiency and governance, where it lags behind more resilient economies like Singapore and New Zealand. However, Indonesia has shown gradual improvements in social development indicators, suggesting a positive trend in human capital development. Conclusion: The study highlights the need for Indonesia to implement significant reforms in market regulation, governance, and social infrastructure to enhance its economic resilience. The findings contribute to the broader understanding of economic resilience in the Asia-Pacific region and provide actionable insights for policymakers aiming to strengthen Indonesia's economic stability and sustainability. Novelty: This study is among the first to apply Briguglio's framework to a comparative analysis of economic resilience across Asia-Pacific countries in the post-COVID-19 context, with a specific focus on Indonesia. The research highlights the unique challenges and opportunities for Indonesia in building economic resilience, providing new insights into the specific areas where policy interventions are most needed.